2021
DOI: 10.1055/a-1387-8334
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Results after Vertebral Body Tethering

Abstract: Vertebral body tethering (VBT), otherwise known as fusion-less anterior scoliosis correction (ASC), is a new and increasingly interesting therapeutic option for selected scoliosis patients. The available data on this surgical technique are still limited and guidelines on patient selection or surgical timing are not available. The aim of this study was to conduct a systematic review of the available literature on VBT. The analysis was performed in accordance with the PRISMA Statement. Nine studies with data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
3
0
2
Order By: Relevance
“…Importantly, the proportion of thoracic versus lumbar tethers in their study is not specified. We propose that with greater mobility in segments distal to the thoracic curve apex, VBT tethers are more prone to breakage, similar to conclusions drawn by Baroncini et al 4 In addition, level-specific factors, including the degree of tension placed over a given segment as well as the amount of remaining vertebral body growth, likely affect the location of tether breaks.…”
Section: Characteristics Of Vbt Breakssupporting
confidence: 83%
See 1 more Smart Citation
“…Importantly, the proportion of thoracic versus lumbar tethers in their study is not specified. We propose that with greater mobility in segments distal to the thoracic curve apex, VBT tethers are more prone to breakage, similar to conclusions drawn by Baroncini et al 4 In addition, level-specific factors, including the degree of tension placed over a given segment as well as the amount of remaining vertebral body growth, likely affect the location of tether breaks.…”
Section: Characteristics Of Vbt Breakssupporting
confidence: 83%
“…2 Spine flexibility and motion are maintained. 2,3 Early studies have demonstrated effective deformity correction-up to 71%-the complication rate was not trivial; 1,[4][5][6][7] the reoperation rate ranges from 3% to 24%. 1,2,5,6 Some reoperations involve the release of the tether secondary to overcorrection.…”
mentioning
confidence: 99%
“…According to the data available in the literature, pulmonary complications after VBT are not uncommon and have been observed in 7–10% of patients [ 1 3 , 7 ]. Commonly reported complications in the literature were recurrent pulmonary effusion, chylothorax, atelectasis, pneumonia, and pneumothorax [ 2 ]. In the presented series, the rate of observed pulmonary complications was much lower than the reported rate in the literature, but the kind of observed complications was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Dazu gehören Korrekturverluste durch Implantatversagen, wie das Reißen der Bandverbindungen "tether breakage", Überkorrekturen im Verlauf und (meist distale) Anschlussdeformitäten im Sinne des "adding on" [10,16,18]. Dies führt zu hohen Revisionsraten von 12%-41%, wobei die Metaanalyse von Shin et al [17] hier auf 14,1% und der systematische Review von Baroncici et al [27] auf 18,9% kommt. Angaben von sekundär additiv erforderlichen klassischen dorsalen Korrekturoperation im Verlauf schwanken zwischen 0°und 13° [15,18,21,22,24,28].…”
Section: Komplikationenunclassified
“…Die Rate an Komplikationen und Reoperationen ist bei dem AVBT ausgesprochen hoch [17,27]. Sie scheint sich zwar mit der Lernkurve zu verringern [30].…”
Section: Zusammenfassungunclassified